Single, double, and triple-hit strategies to establish a long-term premature rabbit model of bronchopulmonary dysplasia - Chiara Catozzi; Francesca Stretti; Enrica Scalera; Matteo Storti; Angelo Modena; Giorgio Aquila; Gino Villetti; Erica Ferrini; Andrea Grandi; Franco Fabio Stellari; Francesca Ravanetti; Luisa Ragionieri; et al. (Respiratory Research)
Abstract Background Bronchopulmonary dysplasia (BPD) is a chronic lung condition of premature neonates, yet without an established pharmacological treatment. The BPD rabbit model exposed to 95% oxygen has been used in recent years for drug testing. However, the toxicity of the strong hyperoxic hit precludes a longer-term follow-up due to high mortality after the first week of life. This study aimed to extend the preterm rabbit model to postnatal day (PND) 14 to mimic the evolving phase of BPD and enable the investigation of therapeutic interventions at later and more relevant time points. Methods Preterm rabbit pups delivered on the 28th day of gestation were either exposed to room air or different degrees of hyperoxia (50% and 70% O2) for 14 days. Single (immediately after birth) or double (at birth and at PND5) intratracheal lipopolysaccharide (LPS) administrations were also tested in combination with 50% O2. Age-matched rabbits delivered vaginally at term were used as controls. Survival, weight gain, lung function, pulmonary artery micro-ultrasound Doppler analysis, lung histology (alveolarization, lung injury score, and design-based stereology), and longitudinal micro-CT imaging were used to compare the outcomes at PND14. Results Premature birth itself, without any other BPD hit, was associated with lung function deficits, delayed lung development, and cardiovascular abnormalities. The BPD-like lung phenotype was enhanced by 70% O2 but not by 50% O2 hyperoxia. Intratracheal LPS delivered immediately after birth was associated with significantly higher lung injury scores at PND14 and increased tissue damping, a marker of parenchymal air resistance. Conclusion Several strategies are feasible to extend the preterm rabbit model of BPD to PND14. Preterm birth at the saccular phase itself, even in the absence of other postnatal BPD hits, was associated with lung function deficits, delayed lung development, and cardiovascular abnormalities compared with age-matched term rabbit pups. Enhanced BPD-like phenotypes can be further achieved by continued exposure to moderate hyperoxia (70% O2) and the intratracheal administration of LPS.